H2S Donors Reverse Age-Related Gastric Malfunction Impaired Due to Fructose-Induced Injury via CBS, CSE, and TST Expression - Pavlovskiy, Yaroslav; Yashchenko, Antonina; Zayachkivska, Oksana (Frontiers in Pharmacology, 2020)
Objective: Excess of fructose consumption is related to life-treating conditions that affected more than a third of the global population. Therefore, to identify the newer therapeutic strategy for the prevention impact of high fructose injury in age-related malfunctions of the gastric mucosa (GM) in the animal model is important. Methods. Adult and aged male rats were divided into control groups (standard diet, SD) and high fructose diet (HFD) groups; acute water immersion restraint stress (WIRS) was induced for evaluation GM adaptive response and effects of testing the therapeutic potential of H2S-releasing compounds (H2S donors). Histological examination of gastric damage was done on hematoxylin-eosin stained slides. Cystathionine beta-synthase (CBS), Cystathionine gamma-lyase (CSE), and Thiosulfate-dithiol sulfurtransferase (TST) activities and oxidative index were assessed during exogenous administration H2S donors: sodium hydrosulfide (NaHS), the novel hybrid H2S-releasing aspirin (ATB-340). The results showed that HFD increased gastric damage in adult and aged rats. HFD-associated malfunction characterized by low activities of H2S key enzymes, inducing increased oxidation. Pretreatment with NaHS, ATB-340 of aged rats in the models of HFD, and WIRS attenuated gastric damage in contrast vehicle-treated group (p < 0.05). The effect of ATB-340 was characterized by reverse oxidative index and increased CBS, CSE, and TST activities. In conclusion, H2S donors prevent GM age-related malfunctions by enhancement CBS, CSE, and TST expression against fructose excess injury though reduction of oxidative damage.